Double-stranded RNA induces disproportionate expression of thymic stromal lymphopoietin versus interferon-β in bronchial epithelial cells from donors with asthma. Issue 7 (13th July 2010) - Uller, Lena; Leino, Marina; Bedke, Nicole; Sammut, David; Green, Ben; Lau, Laurie; Howarth, Peter H; Holgate, Stephen T; Davies, Donna E
Abstract : Background: Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine that strongly activates dendritic cells and can initiate allergic inflammation. Since exposure to rhinovirus or double-stranded (ds) RNA (a surrogate of viral infection) induces TSLP expression in bronchial epithelial cells (BECs), this cytokine may link innate antiviral responses and the type 2 adaptive immune response. Objective: As BECs from donors with asthma have a deficient interferon (IFN) response to rhinovirus infection, a study was undertaken to test the hypothesis that their antiviral response shows a bias towards TSLP production. Methods: Primary BECs were grown from subjects with asthma and healthy volunteers. After exposure to dsRNA, interleukin (IL)-8, IFN β and TSLP mRNA and protein expression were measured by RT-qPCR and ELISA, respectively. Results: dsRNA dose-dependently increased IL-8 expression in BECs with no significant difference between the groups. However, BECs from subjects with asthma expressed less IFN β and more TSLP mRNA and protein in response to dsRNA than BECs from those without asthma (median (IQR) 57 (38–82) pg/ml vs 106 (57–214) pg/ml for IFN β (p<0.05) and 114 (86–143) pg/ml vs 65 (32–119) pg/ml for TSLP (p<0.05) in response to 10 μg/ml dsRNA for 24 h). Induction of TSLP mRNA by dsRNA was blocked by Toll-like receptor 3 or protein kinase inhibitors or by preventing de novo protein synthesis, but not by neutralisation of type I IFN receptors. Conclusion: BECs from subjects with asthma are biased towards higher TSLP and lower IFN β production in response to dsRNA, suggesting that viral infection in asthma may lead to an altered mediator profile that biases towards a Th2 immune response.